Monovalent antibody-conjugated lipid-polymer nanohybrids for active targeting to desmoglein 3 of keratinocytes to attenuate psoriasiform inflammation - Lin, Zih-Chan; Hwang, Tsong-Long; Huang, Tse-Hung; Tahara, Kohei; Trousil, Jiří; Fang, Jia-You (Theranostics, 2021)
To improve the treatment of psoriasiform inflammation, we developed actively targeted nanocarriers loaded with the phosphodiesterase 4 inhibitor AN2728. Methods: Phospholipid-poly(lactic-co-glycolic acid) nanohybrids were prepared and conjugated with monovalent anti-desmoglein 3 antibody to bind keratinocytes. Results: The actively targeted nanohybrids were 229 nm in mean size with a nearly neutral surface charge. Flow cytometry and confocal microscopy showed a 9-fold increase in keratinocyte uptake of targeted nanohybrids relative to non-targeted nanoparticles. The nanoparticles localized mainly in lysosomes after internalization. AN2728-loaded antibody-conjugated nanocarriers inhibited cytokine/chemokine overexpression in activated keratinocytes without affecting cell viability. The targeted nanohybrids also suppressed neutrophil migration by reducing CXCL1 and CXCL2 release from keratinocytes. Following subcutaneous administration in mice, the nanohybrids distributed to the epidermis and hair follicles. In a psoriasis-like skin mouse model, the actively targeted nanoparticles were superior to free drug and non-targeted nanoparticles in mitigating skin inflammation. Intervention with the targeted nanosystem reduced the epidermal thickness of the psoriasiform lesion from 191 to 42 µm, decreased the Psoriasis Area Severity Index by 74%, restored barrier function, and returned chemokine levels to baseline. Conclusions: Our developed nanosystem was safe and demonstrated efficient targeting properties for the treatment of cutaneous inflammation.
Keywords: monovalent antibody; chemokin CXCL2; Animals; keratinocyty; epidermis; zánět; Lysosomes; Epidermis; desmoglein 3; psoriáza; Bridged Bicyclo Compounds, Heterocyclic; kopolymer kyseliny glykolové a mléčné; HaCaT Cells; Keratinocytes; lyzozomy; psoriasis; bicyklické sloučeniny heterocyklické; Nanoparticles; inhibitory fosfodiesterasy 4; Drug Carriers; lidé; fosfolipidy; Phosphodiesterase 4 Inhibitors; Mice; chemotaxe; Antibodies; Boron Compounds; Chemokine CXCL2; vlasový folikul; chemokin CXCL1; nanočástice; myši; lipid-polymer nanohybrid; Inflammation; imunokonjugáty; Hair Follicle; Desmoglein 3; Male; modely nemocí na zvířatech; Neutrophils; Phospholipids; Drug Delivery Systems; keratinocyte; Disease Models, Animal; neutrofily; Chemotaxis; Polylactic Acid-Polyglycolic Acid Copolymer; nosiče léků; Chemokine CXCL1; buněčné linie keratinocytů HaCaT; lékové transportní systémy; zvířata; mužské pohlaví; Immunoconjugates; Psoriasis; sloučeniny boru; protilátky; active targeting; Humans